2011
DOI: 10.1080/09585192.2011.552282
|View full text |Cite
|
Sign up to set email alerts
|

Employee engagement, organisational performance and individual well-being: exploring the evidence, developing the theory

Abstract: The development of mainstream human resource management (HRM) theory has long been concerned with how people management can enhance performance outcomes. It is only very recently that interest has been shown in the parallel stream of research on the link between employee engagement and performance, bringing the two together to suggest that engagement may constitute the mechanism through which HRM practices impact individual and organisational performance. However, engagement has emerged as a contested construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
0
14

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(129 citation statements)
references
References 25 publications
4
111
0
14
Order By: Relevance
“…The primary argument is that the interaction of HPWS at the firm level -employee attitudinal and behavioural responses at the individual level are central to our understanding of the cause-order relationship between HRM and performance (Truss et al, 2013;Paauwe, 2009). According to Dyer and Reeves (1995), an important factor of the HRM-performance relationship is HRM outcomes, that is, employee emotional and behavioural responses and reactions.…”
Section: H2: the Relationship Between Hpwps And Firm Performance Is Smentioning
confidence: 99%
“…The primary argument is that the interaction of HPWS at the firm level -employee attitudinal and behavioural responses at the individual level are central to our understanding of the cause-order relationship between HRM and performance (Truss et al, 2013;Paauwe, 2009). According to Dyer and Reeves (1995), an important factor of the HRM-performance relationship is HRM outcomes, that is, employee emotional and behavioural responses and reactions.…”
Section: H2: the Relationship Between Hpwps And Firm Performance Is Smentioning
confidence: 99%
“…There is an accumulating body of evidence suggesting that "high levels of engagement are associated with high levels of performance, citizenship behaviour and individual wellbeing" (Truss, Shantz, Soane, Alfes, & Delbridge, 2013, p. 2658. However, the identification of a mechanism to enhance employee engagement remains a challenge (Truss et al, 2013).…”
Section: Participative Management Stylementioning
confidence: 99%
“…There is an accumulating body of evidence suggesting that "high levels of engagement are associated with high levels of performance, citizenship behaviour and individual wellbeing" (Truss, Shantz, Soane, Alfes, & Delbridge, 2013, p. 2658. However, the identification of a mechanism to enhance employee engagement remains a challenge (Truss et al, 2013). From an organizational leadership perspective, a significant relationship has been found between participative leadership at supervisor level and employee commitment and trust (Miao, Newman, Schwarz, & Xu, 2013).…”
Section: Participative Management Stylementioning
confidence: 99%
“…A number of studies have shown that employee engagement predicts employee outcomes, organisational success and financial performance (Truss et al 2013). According to a 2004 highperformance workforce study (Arnott and Soobiah 2007a), there is a strong correlation between financial performance and the priority that organisations place on human capital development.…”
Section: Introductionmentioning
confidence: 99%